Al-Namūżaj al-Siyāq fī Ta’līm al-Lugah al-‘Arabiyyah al-Qāim ‘alā Āyāt Mahfūẓah min al-Qur’ān al-Karīm - Rahmi, Wirda; Arani, Samsuar; Zikriati, Zikriati (Study Program of Arabic Language Teaching, 2025)
Arabic language instruction in tahfiz institutions often faces challenges, especially in motivating students to use Arabic for everyday interaction. Many students mainly focus on memorizing Qur’anic verses without connecting them to practical language use. This research aims to develop and implement a contextual Arabic learning model that uses memorized Qur’anic verses as the primary learning resource. The study involved seven second-grade middle school students at Ma’had As-Syahsiah Tahfiz Sains Malaysia and employed a cross-sectional design with pre-test and post-test assessments. Data were collected through observations, tests, and interviews to describe students’ progress in vocabulary, grammar, and communication skills. Univariate analysis was used to present changes in students’ abilities before and after the intervention. The results showed notable improvements in students’ oral and written expression following the application of the contextual Qur’an-based learning model. These findings indicate that linking Qur’anic memorization to contextual language use can enhance students’ linguistic competence and provide an innovative approach to Arabic education in tahfiz institutions and Islamic schools.